Nitrate sources, accumulation and reduction in groundwater from Northern Italy: Insights provided by a nitrate and boron isotopic database. (April 2018) - Martinelli, G.; Dadomo, A.; De Luca, D.A.; Mazzola, M.; Lasagna, M.; Pennisi, M.; Pilla, G.; Sacchi, E.; Saccon, P.
Abstract: Large volumes of precious water resources are negatively affected by nitrate contamination, and the problem of the world population's exposure to this is becoming an even more pressing issue. To tackle this problem, the application of environmental isotopes has proven to be an effective method to identify the N origins and major transformations in different environments. In this work, nitrate (δ 15 NNO3 and δ 18 ONO3 ) and boron (δ 11 B) isotope analyses performed in the last twenty years in groundwater from shallow aquifers of the Po plain area, a complex hydrogeological system of European relevance, have been compiled in a comprehensive database together with major ionic contents; these data were integrated with additional original results, targeting areas not previously examined or complementing the available information. Such data, previously interpreted on the local scale, are examined at the Po plain scale, providing an understanding of the N sources and dynamics in the shallow aquifers, and defining the most important processes governing nitrate contamination in Northern Italy. The most impacted groundwater is that hosted in the alluvial fans of the Alpine and Apennine foothills, due to a combination of high soil permeability and presence of intensive agricultural activities. Here, aquifers are characterized by fast circulation and by great water table depths. On the contrary, nitrate contamination is absent in most low plain areas, with shallow water table depths but lower soil permeability, due to the presence of denitrification processes. The δ 15 N median values, calculated for each province, are significantly correlated with pig density. Hence, manure represents one of the main nitrate sources in groundwater from agriculture, the other being synthetic fertilizers. Isotopic compositions enriched due to denitrification are present in ∼22% of the data, being responsible for nitrate abatement in groundwater affecting up to 70–80% of the original content. The B systematics, in such a low geogenic-B context, proved the presence in the investigated area of another anthropogenic nitrate source of civil origin (i.e. sewage). While new results on the local B sources are reported, the garnering of all groundwater data allowed us to define the range of the expected geogenic B signature (δ 11 B = +13 ± 2.5‰). This contribution is a significant step forward for the use of the coupled δ 15 N - δ 11 B toolbox in the study area, previously limited by a poor definition of the compositional end-members. This georeferenced set of hydrochemical and isotopic data will lay the foundations for future monitoring activities and advanced data treatment or modelling. In addition, since the hydrogeological setting of the investigated area shows common features to alluvial basins located near mountain ranges, the approach and the results presented in this study serve as a reference for other study areas worldwide. Graphical abstract: Image 1 Highlights: 648 δ 15 NNO3, 403 δ 18 ONO3 and 27 δ 11 B georeferenced groundwater data discussed. δ 15 N median values are significantly correlated at the basin scale with pig density. Nitrates are absent in most low plain areas due to denitrification. δ 11 B data proved the presence of a contamination by sewage. The expected geogenic δ 11 B in the Po plain is +13 ± 2.5‰ vs NBS-951.